Comparison of on-chip MIS capacitors based on stacked HfO2/Al2O3 nanolaminates. (December 2022) - Kartci, Aslihan; Vancik, Silvester; Prasek, Jan; Hrdy, Radim; Schneider, Michael; Schmid, Ulrich; Hubalek, Jaromir
Abstract: High- κ dielectric materials are commonly used in microelectronic components due to the technological necessity of increasing the capacitance density of dielectric layers. The thickness of the layer is a crucial parameter of this technology because it has a significant influence on dielectric properties, capacitance density, leakage current density–voltage ( J–V ), breakdown voltage, and capacitance density–voltage ( C–V ). Among metal oxide compounds, HfO2 and Al2 O3 have been widely studied due to their good thermodynamic stability in contact with silicon. Thus, in this study, devices are fabricated by atomic layer deposition (ALD) processes on Si wafer. Properties of HfO2 /Al2 O3 -based stack dielectric as on-chip MIS capacitors are investigated. The capacitance density, C–V, J–V, impedance characteristics, equivalent dielectric constant, breakdown voltage, and leakage current are studied on stacks (HfO2 /Al2 O3 ) with a thickness ratio of 1:1. The experimental results indicate very good leakage current and good breakdown voltage. Oxygen vacancies play a significant role in increasing the conductance and contrarily decreasing the equivalent dielectric constant of the stack. Graphical abstract: